2022
DOI: 10.1002/ehf2.14167
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker profiles in heart failure with preserved vs. reduced ejection fraction: results from the DIAST‐CHF study

Abstract: Aims Chronic heart failure (HF) is a common disease and one of the leading causes of death worldwide. Heart failure with preserved ejection fraction (HFpEF) and with reduced ejection fraction (HFrEF) are different diseases with distinct as well as comparable pathophysiologies and diverse responses to therapeutic agents. We aimed to identify possible pathobiochemical signalling pathways and biomarkers in HFpEF and HFrEF by using a broad proteomic approach. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…We found the following top 3 associated ‘biological processes’ per intercept subset, for subset A: intracellular transport (B–H pval: 8.79E-15), protein translation (1.43E-14) and peptide biosynthetic process (1.43E-14); for subset B, regulation of chromosome segregation (1.94E-02) and regulation of sister chromatid segregation (4.32E-02); for subset C, adaptive immune response (1.59E-02), humoral immune response mediated by circulating immunoglobulin (1.59E-02), immune effector process (1.59E-02); and for subset D, cell adhesion (2.38E-18), locomotion (2.12E-13) and taxis (6.25E-13). Biological processes that were previously found to be highly associated with HFrEF in other studies making use of the Gene Ontology database, 23 , 24 were also reflected in our subsets. Peptidyl-serine phosphorylation (1.19E-02) was associated with subset A, and plasma membrane bounded cell projection morphogenesis (1.70E-07), ERK1 and ERK2 cascade (1.92E-04), response to wounding (1.75E-03), mesenchyme development (2.94E-02), and MAPK cascade (3.18E-02) were associated with subset D.…”
Section: Resultssupporting
confidence: 57%
“…We found the following top 3 associated ‘biological processes’ per intercept subset, for subset A: intracellular transport (B–H pval: 8.79E-15), protein translation (1.43E-14) and peptide biosynthetic process (1.43E-14); for subset B, regulation of chromosome segregation (1.94E-02) and regulation of sister chromatid segregation (4.32E-02); for subset C, adaptive immune response (1.59E-02), humoral immune response mediated by circulating immunoglobulin (1.59E-02), immune effector process (1.59E-02); and for subset D, cell adhesion (2.38E-18), locomotion (2.12E-13) and taxis (6.25E-13). Biological processes that were previously found to be highly associated with HFrEF in other studies making use of the Gene Ontology database, 23 , 24 were also reflected in our subsets. Peptidyl-serine phosphorylation (1.19E-02) was associated with subset A, and plasma membrane bounded cell projection morphogenesis (1.70E-07), ERK1 and ERK2 cascade (1.92E-04), response to wounding (1.75E-03), mesenchyme development (2.94E-02), and MAPK cascade (3.18E-02) were associated with subset D.…”
Section: Resultssupporting
confidence: 57%
“…Of the 5131, we excluded 5104 articles, leaving 27 for full-text screening. After completing the full-text screening, we excluded 17 articles leaving 10 eligible articles, which we then assessed for risk of bias [ 10 , 11 , 13 , 15 , 16 , 27 31 ]. One of the 10 articles was excluded after the risk of bias assessment (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 10 , 13 , 15 ] utilized the SomaScan aptamer platform which is reported as having a wider human proteome coverage [ 37 , 38 ]. Six studies [ 11 , 16 , 27 , 28 , 30 , 31 ] used Olink antibody-based assay which is reported to have stronger protein target specificity based on the percentage of proteins on the platform with reported genetic association [ 37 ]. However, all six antibody-based studies used panels containing only a subset (3–15%) of the 3072 Olink Explore panel while aptamer studies reported the full array of proteins available on their respective SomaScan versions.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the initiation of anticoagulation, it is important to take into account the CHA2DS2-VASc score. This scoring system evaluates the risk of stroke based on comorbidities and other relevant risk factors [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…Due to the intricacy of HFpEF, there are difficult therapeutic problems that are made even more difficult by the lack of specific, effective pharmacological treatments. Contrary to HFrEF, which has benefited from medicinal treatments based on clinical guidelines such as beta-blockers and angiotensin-converting enzyme inhibitors, HFpEF lacks targeted treatments with proven efficacy [ 6 ]. As a result, individuals with HFpEF frequently have limited reactions to standard heart failure drugs, resulting in insufficient symptom alleviation and unfavorable clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%